Deviant teachings in Malaysia and theirs interpretation of the Qur’an - Fadzil, Ammar (Centre for Promoting Ideas, USA, 2011)
The Qur'an is the most important source for the Muslim sects throughout the Islamic history. They have to return to it either to understand its wisdom or to find support for their doctrine. Hence it has been noticed that there is no any Muslim sects save they would have verses from the Qur'an on which their doctrine would be based. In Malaysia, deviant teachings have attracted the concern of Islamic authorities. The issue is these deviant teachings have used some of the Qur'anic verses and misinterpreted them to advocate their objectives. It is the aim of this article to study these matters focusing on a number of topics as follows: the rule of Qur'anic interpretation, the meaning of deviant, the misinterpretation of the Qur'an, the tafsir works in Malaysia, and the examples of deviant teachings in Malaysia and their interpretation of the Qur'an.